Self-Instructional Training Application on Diabetic Patients' Self-Care Behaviors - Wahyuni, Sri; Prasetyowati, Christina Dewi; Pratiwi, Wahyu Nur; Alfiadi, Khalid (Department of Nursing, Faculty of Medicine, Diponegoro University, 2021)
Background: The diabetes mellitus cases have significantly increased in Indonesia over recent years. Health education for patients has often been carried out; however, education using self-instructional methods, which provided self-learning to solve problems by adjusting the patient's ability to improve self-care behaviors, has not been widely used.Purpose: This study aimed to analyze the self-care behaviors of diabetic patients with the application of self-instructional training.Methods: This research was a quasi-experimental study with a non-equivalent pretest-posttest with a control group design. The participants were 73 diabetic patients in the out-patient units selected by a purposive sampling technique, and divided into two groups: the intervention group (n=37) and the control group (n=36). The intervention group received a self-instructional training program which was carried out in two sessions using a booklet; each session lasted for 45 minutes. The Summary of Diabetes Self-Care Activities (SDSCA) questionnaire was used to collect diabetic patients' self-care behavior data. Wilcoxon and Mann-Whitney tests were employed for data analysis.Results: Self-care behaviors of patients with diabetes mellitus increased before and after the training in both groups (p=0.000). However, the increase in the intervention group was higher than that in the control group, from 46.46±5.014 to 58.03±7.320 and from 47.78±4.929 to 51.64±6.406, respectively. There was also a significant difference in the self-care behaviors of diabetic patients between the intervention group and the control group (p=0.000).Conclusion: Self-instructional training significantly improves self-care behaviors of diabetic patients. Therefore, self-instructional training can be considered to apply in the clinical setting for improving self-care behaviors of diabetic patients to prevent complications, and for enhancing nursing care of diabetes mellitus.